Use of screens, books and adults’ interactions on toddler’s language and motor skills: A cross-cultural study among 19 Latin American countries from different SES - Lucas G. Gago-Galvagno; Angel M. Elgier; Angel J. Tabullo; Edson J. Huaire-Inacio; Angela M. Herrera-Alvarez; Carmen Zambrano-Villalba; Frania R. López; Emmanuel Herrera-González; Olivia Morán-Núñez; Neyra J. Ochoa-Vega; Chrissie Ferreira de Carvalho; Rosario Spencer; et al. (PLoS ONE, 2025)
Children’s screen use is ubiquitous, with toddlers in particular demonstrating increases after the pandemic and negative associations with cognitive abilities. Thus, the objective of this cross-cultural study was to broaden and deepen existing results by describing Latin American toddlers’ screen use and its association with parental reports of language skills, developmental milestones, and sociodemographic variables. A sample of 1878 toddlers from 12 to 48 months (M.age = 27.55, SD = 9.68, male = 933, low-SES = 945) from 19 different Latin American countries was evaluated. Parent-report measures of children’s use of screens, SES, language, and developmental milestones were administered virtually or face-to-face. Results indicated that infants’ screen exposure times were longer than recommended, with TV and smartphone being the most frequent screen media among them. Also, most of the screen time was shared with an adult. These results were consistent across parent-reported SES and nationality. In addition, negative and significant associations were generally found between screen time and language skills, which were in turn positively associated with shared reading times. The frequency of shared screen use with adults demonstrated positive correlations with language skills, after controlling for sociodemographic variables. Lastly, entertainment and educational content was associated with higher levels of language skills compared to music. In conclusion, this study demonstrates the importance of promoting responsible and accompanied use of screens with age-appropriate content during the first years of life across different contexts.